2021
DOI: 10.1101/2021.03.11.434922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pangenome of the fungal pathogenNeonectria neomacrospora

Abstract: The fungal plant pathogen Neonectria neomacrospora (C. Booth & Samuels) Mantiri & Samuels (Ascomycota, Hypocreales) is a bark parasite causing twig blight, canker, and in severe cases, dieback in fir (Abies spp.). Although often described as a mild pathogen, foresty and phytosanitary agencies have expressed their concern for potential economic impact. Two epidemics caused by this species are known: one from eastern Canada and one current within Northern Europe. We present key genome features of N. neom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…This was first studied within yeasts such as Saccharomyces cerevisiae (63% of orthologs in the core genome of >1k genomes; Peter et al 2018 ), Cryptococcus neoformans , and Candida albicans (80–90% orthogroups form the core genome; McCarthy and Fitzpatrick 2019 ). More recent work with multicellular fungi has found a similar level of genomic conservation ( Zymoseptoria tritici , Badet et al 2020 ; Rhizoctonia solani , Kaushik et al 2020 ; and Neonectria neomacrospora , Nielsen et al 2021 ). Studies that consider a wider diversity of genomes have also found maintenance of a high percentage of gene orthogroups ( Okagaki et al 2016 ; Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…This was first studied within yeasts such as Saccharomyces cerevisiae (63% of orthologs in the core genome of >1k genomes; Peter et al 2018 ), Cryptococcus neoformans , and Candida albicans (80–90% orthogroups form the core genome; McCarthy and Fitzpatrick 2019 ). More recent work with multicellular fungi has found a similar level of genomic conservation ( Zymoseptoria tritici , Badet et al 2020 ; Rhizoctonia solani , Kaushik et al 2020 ; and Neonectria neomacrospora , Nielsen et al 2021 ). Studies that consider a wider diversity of genomes have also found maintenance of a high percentage of gene orthogroups ( Okagaki et al 2016 ; Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 85%